THE VIOLATION OF ENGLISH PRONUNCIATION PRACTICED BY THE GRADE NINTH STUDENTS OF SLUB SARASWATI DENPASAR - Eka Dian Rahmanu, I Wayan (Yavana Bhasha : Journal of English Language Education, 2018)
Pronunciation is the way a word or a language is spoken, or the manner in which someone utters a word. If one is said to have correct pronunciation, then it refers to both within a particular mispronunciation. Many students usually make the mistake in pronouncing even the simple words. The researchers choose the students of SLUB Saraswati Denpasar as the research objects because they are in bilingual class that should use English better than others. The title of this research is ‘The violation of English pronunciation practiced by the grade ninth students of SLUB Saraswati Denpasar’.Based on the background of the study, the problem of the research can be formulated as follows: (1) how do the students pronounce selected words in English? (2) how do the students violate the pronunciation of English words? (3) What is the cause of their miss-pronunciation? In this research we use the main theory English phonology by April McMahon and Gerald Kelly.The method of this research is qualitative research which explains the analysis in description. The data of this research had been taken from 10 students of grade ninth SLUB Saraswati Denpasar. The researchers used the classroom action research to collect the data. They are collected by recording the pronunciation of the students.In general, the results are: 75% students miss-pronounced the selected words, meanwhile 25% students pronounced almost correctly. From 13 selected words, 30% words among those words were miss-pronounced by the students and 70% were pronounced correctly. The students do the miss-pronunciation mainly because the lack of knowledge in pronouncing the words. Keywords: violation, pronunciation and students